Facile synthesis of 3D Fe2O3 nanostructures: sponge-like cube shape and bird nest-like architecture - Tran, Quy Phuong; Ho, Van Minh Hai; Tran, Thai Hoa; Nguyen , Duc Cuong (Hue University Journal of Science: Natural Science, 2023)
The hierarchical nanostructures (3D) with their large specific surface area and abundant pores usually possess unique physical and chemical properties for various important applications. In this report, we have introduced simple and scalable routes to successfully synthesize 3D iron oxide nanostructures, including porous cubes and bird nest-like architecture. The 3D sponge-like Fe2O3 nanocubes were formed by an annealing process of perfect Prussian Blue (PB) microcubes, which were built from small nanoparticles linked together. Whereas, the 3D bird nest-like Fe2O3 nanostructures were formed by the transformation of C@FeOOH nanoflower precursors, which were constructed by primary nanorods. The results indicated that the obtained materials show monodispersity, uniform morphology, ultra-porosity and extremely high specific surface area. With unique characteristics, the 3D Fe2O3 nanostructures could be potential candidates for various important fields such as catalysts, absorption and gas sensors.